KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 7 PADANG - Dewi, Puspita; Afnita, Afnita (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT There are three aims of this study. First, describe the skills of reading comprehention to the news of VIII grade students at SMP Negeri 7 Padang. Second, describe the writing text skills of VIII grade students at SMP Negeri 7 Padang. Third, describe the correlation of reading comprehention to the news with the writing text skills of VIII grade students at SMP Negeri 7 Padang. The  type of this research is quantitative in terms of descriptive methods. The design used in this study is correlational design. The population of this study was the eighth grade students of the SMP Negeri 7 Padang which was registered in the 2018/2019 school year, it was 254 students. The sample in this study was determined by proportional random sampling of 15% of the population, namely 40 students. The research data is in the form of scores on the skills test results of reading comprehention to the news and scores on the results of the test writing news text skills. The instrument of this study is an objective test to measure news reading comprehention skills and performance tests to measure news text writing skills. The results of this study are three. First, the skills to write news texts of  VIII grade students of the SMP Negeri 7 Padang is in accordance with the Good qualifications (B) with an averange value 81,25. Second, the skill of reading comprehention to the news text of VIII grade students of the SMP Negeri 7 Padang in accordance with Good qualifications (B) with an averange value 81,37. Third, there is a significant correlation betwen reading comprehention skills and news text writing skills of VIII grade students of the SMP Negeri 7 Padang on n-1 freedom degrees and 95% significant level. H0 is reject and H1is accepted because the tcount is greater than ttable (4,49>2,68).             Kata Kunci: korelasi, keterampilan membaca pemahaman, keterampilan menul   teks berita